2018
DOI: 10.1097/meg.0000000000001073
|View full text |Cite
|
Sign up to set email alerts
|

High rate of acute pancreatitis during the Ramadan fast

Abstract: We found a high rate of AP in the fasting population during the Ramadan. Physicians should be aware of this link and suspect it for fasting patients presenting with epigastric pain during the Ramadan fast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…However, there was no difference between the two sexes in terms of the decrease in the rate of cholecystitis. Our results concur with the findings of Genady et al that the rate of acute pancreatitis rose during the period of Ramadan (10). It was stated that there was a statistically significant difference between those did and did not fast during Ramadan.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, there was no difference between the two sexes in terms of the decrease in the rate of cholecystitis. Our results concur with the findings of Genady et al that the rate of acute pancreatitis rose during the period of Ramadan (10). It was stated that there was a statistically significant difference between those did and did not fast during Ramadan.…”
Section: Discussionsupporting
confidence: 93%
“…It was stated that there was a statistically significant difference between those did and did not fast during Ramadan. However, they did not show any difference between females and males (10). It was also reported that the rate of acute pancreatitis and cholangitis increases in patients with eating disorders (11).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In 2018, four reports addressed the ED workload and four specific clinical scenarios. [79][80][81][82][83][84] The activities of emergency services and patient characteristics were examined in two studies from the UAE and Lebanon. From an adult and pediatric ED in the UAE, the hourly arrivals, census, and visit characteristics were retrospectively compared for Ramadan versus non-Ramadan periods over 4 years (2010-2013) by Balhara et al [79] Hourly arrivals and census and differences in characteristics were examined.…”
Section: Medical Emergencies During Ramadanmentioning
confidence: 99%